ANALISIS PEMBENARAN INTERNAL (INTERNAL JUSTIFICATION) PADA TINDAKAN MENYONTEK DI KALANGAN MAHASISWA - Idawati, Kurnia; Fitriani, Nurul; Sulaeman, Karina Adinda (Diglosia : Jurnal Pendidikan, Kebahasaan, dan Kesusastraan Indonesia, 2023)
The aim of this research is to reveal justifications the students made when they cheated on their academic tasks as well as the analysis in the aspects of educational psychology and collectivism culture on those justifications. The research method is qualitative interpretive on quantitative data obtained through a written survey. From the research results, various motives or reasons as justifications for the students to cheat can be grouped into two categories, namely the "lazy" motive which includes the "not learning" and "in a tight spot" motives; and the â€œout of ideasâ€ motive which includes â€œlack of confidenceâ€, â€œfear of bad gradesâ€, â€œneeds instant gradesâ€, and â€œforgetting the material being studiedâ€. The two categories can be seen from the psychological point of view, especially educational psychology. The first category is motivated by, among others, a lack of self-concept and lack of self-determination, while the second category is due to a lack of self-efficacy. Almost all types of cheating motives refer to internal justifications. Internal justification is the hallmark of an interdependent collectivism culture. Four aspects of collectivism culture that can be used to analyse this internal justification are â€œharmony should always be maintainedâ€, â€œrelationship prevails over taskâ€, "Weâ€“consciousnessâ€, and â€œtransgression of norms leads to shame feelingsâ€.Keywords: academic cheating, internal justification, educational psychology, collectivism culture